Investigating the association between diabetes and carpal tunnel syndrome: A systematic review and meta-analysis approach. - Elaheh Sanjari; Hadi Raeisi Shahraki; Lusine Khachatryan; Abdollah Mohammadian-Hafshejani (PLoS ONE)
Introduction In recent years, several studies have reported on the relationship between diabetes and carpal tunnel syndrome (CTS). However, due to their contradictory results, a systematic review and meta-analysis were conducted to investigate this subject. Methods This study is a systematic review and meta-analysis of studies published in ISI Web of Science, Scopus, PubMed, Cochrane, Google Scholar, and Embase databases. Heterogeneity in the studies included in the meta-analysis was evaluated using statistical tests such as the Chi-square test, I2, and forest plots. Publication bias was assessed using Begg's and Egger's tests. Results This investigation analyzed data from 42 studies conducted between 1985 and 2022, with a total of 3,377,816 participants. The meta-analysis demonstrated that the odds ratio (OR) of CTS in participants with a history of diabetes compared to those without was 1.90 (95% CI: 1.64-2.21; P-value < 0.001). Given that publication bias was observed in this study (Begg's test P-value = 0.01), the modified OR was calculated with consideration of missed studies, which was 1.68 (95% CI: 1.45-1.94; P-value < 0.001). Conclusion The results of this study suggest that diabetic patients have 90% higher odds of developing CTS compared to non-diabetic individuals, which is statistically significant.